Effect of friction on vibrotactile sensation of normal and dehydrated skin. Issue 1 (17th March 2015) - Chen, S.; Ge, S.; Tang, W.; Zhang, J.
Abstract : Background: Vibrotactile sensation mediated is highly dependent on surface mechanical and frictional properties. Dehydration of skin could change these properties. Objectives: To investigate the relationship between friction and vibrotactile sensation of normal and dehydrated skin. Methods: Vibrations were firstly measured during surface exploration using a biomimetic sensor. Piglet skin was used as human skin model to study frictional properties for both normal and dehydrated skin using an atomic force microscope on nanoscale and a pin‐on‐disk tribometer on macroscale. Effect of vibrational frequency on friction and vibrotactile perception was also observed on nano and macro scale for normal and dehydrated skin. Results: The result indicated that dehydrated skin was less sensitive than normal skin. The coefficient of friction of dehydrated skin is smaller than that of normal skin on both nano and macro scale. The coefficient of friction increases as increasing scanning frequencies. Conclusion: There is a positive correlation between coefficient of friction and vibrotactile sensation on nanoscale and macroscale.